Pengembangan Usaha Kecil Menengah di Tanggulangin Sidoarjo - Moch Mahrus Fathur Rosy; Refita Avitriani Rizalina; Mega Ayu Ningtyas (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2018)
The business development of leather handicraft SME entrepreneurs in Tanggulangin does not take place instantly. In the beginning, entrepreneurs attended various training in the development of skin-based SMEs. After his knowledge was sufficient then he applied it in the field. Here the high creative power of entrepreneurs is required. With such diverse creative powers, the demand for their products will increase. The level of production increases due to increased demand from consumers. This increasing demand is the beginning of economic development at Tanggulangin so that employers need a lot of employees. If many residents in Tanggulangin are absorbed into the SME leather handicraft center, the unemployment and poverty there will automatically decrease. Each family member has high productivity because a lot of it is absorbed into the leathercraft UKM center. The higher the level of productivity of the residents there, the more evenly the income per family there, and the standard of living will increase. Tanggulangin's income and income levels increase along with the advancement of UKM there. This can be an income from the city of Sidoarjo itself if the revenue from Tanggulangin continues to be constant from year to year.